2020
DOI: 10.1080/13501763.2020.1712462
|View full text |Cite
|
Sign up to set email alerts
|

Governance through real-time compliance: the supranationalisation of European external energy policy

Abstract: Member States have retained core competences in external energy policy since the beginning of European integration. Even the new 'energy chapter' in the Lisbon Treaty safeguards national prerogatives. Contrasting this trend, we show that throughout the past decade this national stronghold has been eroding and replaced by supranational oversight. Reviewing energy-related negotiations of Poland and Lithuania with Russia and new regulation on intergovernmental agreements, we demonstrate how the Commission gained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 39 publications
(38 reference statements)
2
6
0
Order By: Relevance
“…The observations described above may additionally contribute to weakening the cohesion of the European Union, which can already be observed in the case of Hungary, which denies the demand to resign from the supply of energy resources from Russia. This process has also already been noticed by Thaler and Pakalkaite (2021) and Keypour and Ahmadzada (2022).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The observations described above may additionally contribute to weakening the cohesion of the European Union, which can already be observed in the case of Hungary, which denies the demand to resign from the supply of energy resources from Russia. This process has also already been noticed by Thaler and Pakalkaite (2021) and Keypour and Ahmadzada (2022).…”
Section: Discussionsupporting
confidence: 73%
“…In light of the research results received and to date, it can also be concluded that the current situation of the energy commodity market Europe is not conducive to the tightening of EU climate policy. The EU's actions in this regard were criticized already before the outbreak of the war in Ukraine, as clearly indicated by the considerations conducted by Hofmann and Staeger (2019); Thaler and Pakalkaite (2021); Solorio and Jörgens (2020) and Keypour and Ahmadzada (2022).…”
Section: Discussionmentioning
confidence: 99%
“…Through governance architectures, the European Commission steers the development and implementation of sectoral policies and their underlying problem formulations, values and adopted behaviours. As research has demonstrated, with such soft means, the Commission is gradually able to expand its procedural leeway beyond its mandate (Terpan, 2015; Thaler & Pakalkaite, 2021), up to the point of a supranational ‘competence creep’ as observed by legal scholars (Garben, 2019; Weatherill, 2004). Taking this into account, we suggest that crises provide an opportunity for the European Commission to infuse normative reconfigurations within EU governance architectures and thus ‘be able to push their agenda even when they are lacking the formal authority to do so’ (Debre & Dijkstra, 2021, p. 10; also see Kreuder‐Sonnen & White, 2022).…”
Section: Theoretical Integration: Norms and Crises In Eu Governancementioning
confidence: 99%
“…On the other hand, even though the Member States prefer to have control over energy policy issues, especially in times of crises, the European Commission found a way to expand supranational authority with the institutionalisation of new instruments centred on "real-time compliance" (Maltby 2013;Thaler and Pakalkaite 2020). Indeed, this strategy is closely related to the European Commission's wider institutionalised efforts to prevent non-compliance (Falkner 2018;Scholten 2017), which still remains a "black box" (Versluis 2007).…”
Section: The Europeanisation Process: a Theoretical Contextmentioning
confidence: 99%